Exploratory Study of MYD88 L265P, Rare NLRP3 Variants, and Clonal Hematopoiesis Prevalence in Patients With Schnitzler Syndrome. Issue 12 (14th October 2019) - Pathak, Shelly; Rowczenio, Dorota M.; Owen, Roger G.; Doody, Gina M.; Newton, Darren J.; Taylor, Claire; Taylor, Jan; Cargo, Catherine; Hawkins, Philip N.; Krause, Karoline; Lachmann, Helen J.; Savic, Sinisa
Abstract : Objective: To assess the prevalence of the MYD 88 L265P mutation and variants within NLRP3 and evaluate the status of oligoclonal hematopoiesis in 30 patients with Schnitzler syndrome (SchS). Methods: Thirty patients with SchS were recruited from 3 clinical centers. Six patients with known acquired cryopyrin‐associated periodic syndromes (aCAPS) were included as controls. Allele‐specific oligonucleotide–polymerase chain reaction was used for the detection of the MYD 88 L265P variant, next‐generation sequencing was applied to analyze NLRP3 and 28 genes associated with myelodysplastic syndrome, and gene scanning was performed for the detection of X chromosome inactivation. Results: Activating NLRP3 mutations were not present in 11 SchS patients who had not been sequenced for this gene previously. The MYD 88 L265P variant was present in 9 of 30 SchS patients, and somatic mutations associated with clonal hematopoiesis were identified in 1 of 30 patients with SchS and 1 of 6 patients with aCAPS. Evidence of nonrandom X chromosome inactivation was detected in 1 female patient with SchS and 1 female patient with aCAPS. Conclusion: A shared molecular mechanism accounting for the pathogenesis of inflammation in SchS remains elusive. Clonal hematopoiesis is not associated with other somatic mutations found in individuals with SchS or aCAPS.